EVOLUTION OF STRATEGY AND METHODS OF TERRORIST ACTIVITY IN THE EUROPEAN COUNTRIES - TseluykoМ. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The stages and methodology of terrorist activity in the European countries have been investigated from the beginning of the origin of terrorism in its modern understanding. The strategy, tactics and methods of terroristic acts realization, which are typical for every wave of terrorism in Europe, have been revealed. Among those are the basic evolutional changes and their dependence on several factors.